A customized allogenic bone block for alveolar reconstruction quantitated by a 3D matching technique: A case report. Issue 9 (12th September 2021) - Blume, Oliver; Back, Michael; Martin, Kim; Windisch, Péter
Abstract: After initial resorption, the bone volume showed long‐term stability following loading of the implant. Furthermore, 3D matching was a suitable quantification method to analyze the volume development of bone augmentation. Abstract : After initial resorption, the bone volume showed long‐term stability following loading of the implant. Furthermore, 3D matching was a suitable quantification method to analyze the volume development of bone augmentation.